Universal study of Three Product Inventory Model With Production by Two-Unit System and Sales - Kanagajothi, D.; Srinivasaragavan, S.; Parvathi, S. (International Journal of Engineering and Technology, 2018)
This paper is dedicated to the analysis of two (s, S) inventory systems. In this paper we study three different products inventory systems when productions of three different products are done alternately. The products are produced by a two-unit system with exponential failure and repair times. The sales time starts when k sets of the three different products are produced or when the two unit system fails. The double Laplace transform of the probability density function of the time to start sales and sales time and their means are obtained. Numerical examples are presented with MATLAB ODE Tool.Â Â
Keywords: Inventory systems; Production models; stochastic models; Two-unit systems.